Using English Movies to Enhance Grade XI Students‟ Speaking Skill (A Classroom Action Research Conducted in SMAN 1 Seyegan, Sleman) - Aeni, Noor; Arini, Restu ((JELE) Journal Of English Language and Education, 2015)
This research intended to discover two things, namely the students‟ interest inlearning English by using movies watching media, and the result of the students‟speaking skill improvement on cyclical implementations. This research appliedClassroom Action Research proposed by Kemmis and McTaggart (2000) with twocycles. Each cycle consisted of a pre-test, treatments, and post-tests. It involved 31students of XI IPA 3 class in SMAN 1 Seyegan as the research subjects. The result ofthis research showed that English movies could make the students interested infollowing the English class. It was proven by the students who became more active totalk in English and did not feel shy or reluctant to share their thoughts. Another resultshowed that the students‟ average score was gradually improved from 58.08 in the pretestbecame 65.74 and 74.78 in the first and second post-tests. It can be concluded thatEnglish movies is effective to be implemented as an alternative teaching and learningmedia to teach English speaking skill. Therefore, English teachers are recommended touse English movies to optimize the English learning outcome not only on speaking skillbut also other skills.Keywords: Classroom Action Research, English Movies, Improve, Speaking Skill